In silico analysis of CSF2RB from cancer genomic databases reveals a heterogeneous role in different breast cancer subtypes - Alshelaiel, Raghad; Alkushi, Abdulmohsen; Alriyees, Lolwah Abdullah; Alamro, Abir Abdullah; Alanazi, Humidah; Alhareeri, Areej; AlMuzzaini, Bader; Rashid, Mamoon (Frontiers in Bioinformatics, 2025)
ObjectiveCSF2RB is the common beta chain of the heterodimeric receptors for the cytokines, granulocyte–macrophage colony-stimulating factor (GM-CSF), interleukin 3 (IL-3), and interleukin 5 (IL-5). The activation of these cell surface receptors results in functional responses including cellular proliferation, differentiation, survival, and maturation via multiple signaling pathways such as JAK2/STAT5, MAPK, and PI3-kinase/AKT. Moreover, CSF2RB is abnormally expressed in a variety of tumors, especially in leukemia. The implications of CSF2RB in breast cancer remain unclear and have not been widely studied.MethodsWe analyzed CSF2RB genetic changes, mRNA expression, DNA methylation, prognosis, and immune infiltration levels across different tumor types, with a focus on breast and hematological malignancies. The data used in this study were obtained from publicly available cancer genomics databases, such as TCGA, cBioPortal, TIMER2.0, GEPIA, and UALCAN.ResultsOur in silico analyses showed overexpression of CSF2RB in acute myeloid leukemia (AML) and decreased expression in breast invasive carcinoma (BRCA) compared to matched normal samples. Promoter methylation of CSF2RB was elevated in BRCA samples compared to normal samples. Our analysis further demonstrates that the CSF2RB gene has a favorable prognostic effect in BRCA, although this was not statistically significant across all databases studied. We found that BRCA and its subtypes exhibit high CD8+ T-cell infiltration levels that are positively correlated with the CSF2RB gene expression level. Wild-type CSF2RB shows higher expression than the mutated CSF2RB in breast cancer. CSF2RB expression (and/or mutation) has no significant effect on the overall survival probability. CSF2RB expression is downregulated in luminal and HER2-positive samples but upregulated in triple-negative breast cancer (TNBC), compared to that in normal samples.ConclusionThe results suggest a diverse role for the CSF2RB gene across different subtypes of breast cancer. To attribute a clear role to CSF2RB in breast cancer, further functional studies focusing on differential gene expression, methylation, and their prognostic effect in each breast cancer subtype are required.